compare $a=2016^\sqrt{2014}, b=2015^\sqrt{2015},c=2014^\sqrt{2016}$

I took 2 functions to solve this question:

$f(x)=\sqrt{x+1}\ln(x-1)-\sqrt{x}\ln x$ and $g(x)=\sqrt{x}\ln x - \sqrt{x-1}\ln(x+1).$

$f(x)$ has a local maxima at a point of abscissa $x_1\in(62,63)$ and $\lim_{x\to\infty}f(x)=0$ and $f'(x)<0$ on $[x_1,\infty).\implies f(2015)>0\implies c>b.$

$g(x)$ has a local maxima in the point of absicssa $x_2\in(45,46), \lim_{x\to\infty}g(x)=0$ and $g'(x)<0$ on $[x_2,\infty)\implies g(2015)>0\implies b > a.$

Leaving us with the answer $c > b > a.$

However, I was thinking of a way of verifying this (comparing these numbers) using only $1$ function and I was thinking maybe something like $f(x)=\sqrt{x}\ln(4030+x)...$ but it doesn't really work out... how could i compare these numbers using only one function?

  • $\begingroup$ is the function $f(x)=\sqrt{x}\ln(4030-x)$ instead? $\endgroup$ – Ginger88895 Jun 7 '18 at 7:08
  • $\begingroup$ $f(x)= x^{\frac1{\sqrt x}}$ $\endgroup$ – Lord KK Jun 7 '18 at 7:19

Consider $f(x)=\sqrt{x}\ln(4030-x)$. It is an elementary function, so it is differentiable in $[{2000,3000}]$. Now, $f'(x)=\frac{1}{2\sqrt{x}}\ln(4030-x)-\frac{\sqrt{x}}{4030-x}$.

Intuitively, $\ln(4030-x)$ is way larger than $2$ around $x=2015$, at the same time $\sqrt{x}/(4030-x)\approx \sqrt{x}$ there, so $f'(x)>0$ around $x=2015$, therefore, $c=e^{f(2016)}>b=e^{f(2015)}>a=e^{f(2014)}$, by the monotonicity of the exponential function.

The second paragraph can be made rigorous if required...

  • $\begingroup$ Can you explain a little bit more the second paragraph? and what is the intuition behind $4030$? $\endgroup$ – C. Cristi Jun 7 '18 at 7:51
  • $\begingroup$ I think you mean "rigorous" (not vigorous) although I don't judge... :) $\endgroup$ – stuart stevenson Jun 7 '18 at 12:57
  • $\begingroup$ @C.Cristi: $2014+2016=2015+2015=2016+2014=4030$, so the three numbers fit well $\endgroup$ – Ginger88895 Jun 8 '18 at 9:01
  • $\begingroup$ @stuart stevenson: oops! I will correct it... :P $\endgroup$ – Ginger88895 Jun 8 '18 at 9:05

Take function, $f(x)= x^{\frac1{\sqrt x}}$

$f'(x) = x^{\frac1{\sqrt x}}\times {\frac{2+lnx}{2x^{5/2}}} > 0 $

So, $f(2016) > f(2014) \implies 2016^{\sqrt{2014}} > 2014^{\sqrt{2016}} $

Now, take $g(x) = x^{\frac{1}{\sqrt {x-1}}}$ and $h(x) = x^{\frac{1}{\sqrt {x+1}}}$ and do the same as above.


Let $f(x)=\frac{\ln(x+1)}{\sqrt{x}}$, where $x>2000$.

Thus, $$f'(x)=\frac{\frac{\sqrt{x}}{x+1}-\frac{\ln(x+1)}{2\sqrt{x}}}{x}=\frac{\frac{2x}{x+1}-\ln(x+1)}{2x\sqrt{x}}<\frac{2-\ln(x+1)}{2\sqrt{x^3}}<0,$$ which says $$f(2015)<f(2014)$$ or $$\frac{\ln2016}{\sqrt{2015}}<\frac{\ln2015}{\sqrt{2014}}$$ or $$2016^{\sqrt{2014}}<2015^{\sqrt{2015}}.$$ Now, let $g(x)=\frac{\ln{x}}{\sqrt{x+1}}$, where $x>2000$.

Thus, $$g'(x)=\frac{\frac{\sqrt{x+1}}{x}-\frac{\ln{x}}{2\sqrt{x+1}}}{x+1}=\frac{\frac{2x+2}{x}-\ln{x}}{2(x+1)\sqrt{x+1}}<\frac{3-\ln{x}}{2\sqrt{(x+1)^3}}<0,$$ which says $$g(2015)<g(2014)$$ or $$\frac{\ln2015}{\sqrt{2016}}<\frac{\ln2014}{\sqrt{2015}}$$ or $$2015^{\sqrt{2015}}<2014^{\sqrt{2016}},$$ which says $$a<b<c.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.